Managing for climate change on protected areas: An adaptive management decision making framework. (15th December 2017) - Tanner-McAllister, Sherri L.; Rhodes, Jonathan; Hockings, Marc
Abstract: Current protected area management is becoming more challenging with advancing climate change and current park management techniques may not be adequate to adapt for effective management into the future. The framework presented here provides an adaptive management decision making process to assist protected area managers with adapting on-park management to climate change. The framework sets out a 4 step process. One, a good understanding of the park's context within climate change. Secondly, a thorough understanding of the park management systems including governance, planning and management systems. Thirdly, a series of management options set out as an accept/prevent change style structure, including a systematic assessment of those options. The adaptive approaches are defined as acceptance of anthropogenic climate change impact and attempt to adapt to a new climatic environment or prevention of change and attempt to maintain current systems under new climatic variations. Last, implementation and monitoring of long term trends in response to ecological responses to management interventions and assessing management effectiveness. The framework addresses many issues currently with park management in dealing with climate change including the considerable amount of research focussing on 'off-reserve' strategies, and threats and stress focused in situ park management. Highlights: Managing protected areas for climate change requires structured decision making. Decision making for protected areas must allow managing for change. Decision making must be practical for park managers. Frameworks must integrate climate change, ecological and social knowledge.